2022
DOI: 10.24251/hicss.2022.214
|View full text |Cite
|
Sign up to set email alerts
|

Exploring study profiles of Computer Science students with Social Network Analysis

Abstract: Information technology is widely adapted in all levels of education. The extensive information resources facilitate enhanced human capacity and the social environment to support learning. In particular, Social Network Analysis (SNA) has been broadly used in teaching and learning practices. In this paper, we perform community detection analysis to identify the learning behavior profiles of undergraduate computer science students in a Nordic university. The social network was created using 273 responses to an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Additionally, Sturludottir et al [24] found strong similarities between the networks created by students with the same course choices and their actual major specialization in their latter studies. The changes that a network of a forum community may undergo during an academic year were studied by Tsoni et al [25] and Lopez-Flores et al [26]. These two types of research showed significant changes in graph density (that measures the number of ties between the nodes) and participation.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, Sturludottir et al [24] found strong similarities between the networks created by students with the same course choices and their actual major specialization in their latter studies. The changes that a network of a forum community may undergo during an academic year were studied by Tsoni et al [25] and Lopez-Flores et al [26]. These two types of research showed significant changes in graph density (that measures the number of ties between the nodes) and participation.…”
Section: Related Workmentioning
confidence: 99%